Aplikasi Absensi dengan Mengimplementasikan Scan QR Code Menggunakan Metode Extreme Programming - Alnuria Vanadia Equila; Sholihin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
This employee attendance information system application is designed to simplify the attendance process at CV. DUA SAUDARA SAMUDERA. Both in terms of employee data collection, the process of verifying attendance and reporting of employee attendance recap. In the current system, the employee attendance data collection process is still done manually, where the company's attendance system still uses recording in the attendance book by the company manager. The process of verifying employees who are present must sign the absence which causes a queue at the attendance place. This mobile-based application uses the Dart programming language which is built on the Flutter framework. To speed up performance and change data in real time, the database used is based on NoSQL which is stored in Firebase Cloud Firestore. This employee attendance information system application uses the Scan QR Code feature in the process of verifying participants who are present so that it speeds up the start of employee activities and avoids queues for employee attendance.